Risk Analysis in the Construction Industry Using Project Management Life Cycle and House of Risk - Hidayat, Ananda Syalsabila; Gunarta, I Ketut (Universitas Trunojoyo Madura, 2025)
This study aims to identify risks arising in housing construction projects, particularly those related to budget overruns, and to develop mitigation strategies to ensure that projects run according to plan in terms of cost, time, and resources. The methods used are the Project Management Life Cycle (PMLC) to map the project stages from initiation to closure, and the House of Risk (HoR) to identify risk events and risk agents. The novelty of this study lies in the development of difficulty analysis in HoR, which focuses on three main aspects —cost, time, and resources — that have not been explicitly described in previous studies. The results show that the project experienced a cost increase from IDR 150 million to IDR 165 million due to dominant risks, including misinterpretation of design drawings, fluctuations in material prices, and work delays. Through HoR analysis, priority risks were successfully identified, and mitigation strategies were developed in the form of team training to improve design understanding, control of material usage, and the implementation of contingency planning. This research contributes academically by modifying the HoR method with difficulty analysis based on cost, time, and resources, and integrating it with PMLC. It also provides practical guidance to contractors and project managers on anticipating and managing risks more effectively, thereby improving cost efficiency, timeliness, and resource optimization in housing construction projects.